Mental health service use among people without mental health disorders in the Saudi National Mental Health Survey. Issue 4 (2nd October 2022) - Alangari, Abdulaziz S.; Knox, Sarah S.; Innes, Kim E.; Kristjansson, Alfgeir L.; Wen, Sijin; Bilal, Lisa; Alhabeeb, Abdulhameed; Al-Subaie, Abdullah S.; Altwaijri, Yasmin A.
Abstract: Purpose: To examine the patterns and correlates of 12-month mental health service use among those who do not have a diagnosed mental health disorder during that period in the Kingdom of Saudi Arabia. Methods: The Saudi National Mental Health Survey used the World Health Organization Composite International Diagnostic Interview to ascertain mental health conditions. To understand the reasons for help-seeking among respondents without a diagnosed mental health disorder ( n  = 1256), the patterns and the association of service use to sociodemographic and clinical factors were assessed. Results: Those without a disorder diagnosed comprised 40% of service users accounting for over one-third (35.4%) of mental health service visits. The mean number of visits was higher in those with no indicator of need compared to other categories. General medical provider was the common source of treatment among those without a disorder. Respondents who were ever married were more likely to utilize mental health services, whereas those who reported lower income were less likely to receive treatment. Conclusion: Although the majority of 12-month mental health services were provided to people with a diagnosed disorder or other indicators of need, the proportion of treatment utilized by those who did not is high and warrants further investigation.